Social Capital as the Foundation for the Development of Balo’ Toraja Savings and Loan Cooperative: A Qualitative Study from an Economic Sociology Perspective - Isak Pasulu (Global Research Collaboration, 2026)
The sustainability of community-based cooperatives is influenced not only by financial resources but also by social and cultural factors embedded in the local communities. However, the role of social capital in supporting cooperative development remains insufficiently understood, particularly in culturally rooted institutions. This study aims to analyze the role of social capital in the development and sustainability of the Balo’ Toraja Savings and Loan Cooperative (KSP) from an economic sociology perspective. This study employed a qualitative case study design. Data were collected through in-depth interviews, participant observation, and documentary studies involving cooperative board members, managers, staff, community figures, and cooperative members. Data were analyzed using Miles, Huberman, and Saldaña’s interactive analysis model. The findings show that trust, social norms, and kinship ties function as key forms of social capital that strengthen member participation, maintain institutional stability, and reduce credit risks. Torajan cultural values, particularly siri’ (honor and shame), tongkonan (kinship-based social structure), and kombongan kalua’ (deliberative practice), regulate social and economic behavior within cooperatives. These values strengthen accountability, solidarity, transparency, collective legitimacy, and organizational trust. This study also identifies the challenges associated with social capital, including social pressure, exclusivity, and hierarchical participation. The study concludes that cooperative sustainability is strongly influenced by the institutionalization of social capital within local sociocultural structures. The findings imply that cooperative development should integrate local cultural values with modern governance principles to strengthen institutional resilience and ensure long-term sustainability.